IMPLEMENTASI METODE PEMBELAJARAN ILMU BAHASA ARAB BAGI PEMULA BERBASIS KITAB DL 1 MENGGUNAKAN MODUL BELAJAR BERPOLA DEEP Q&A SEBAGAI UPAYA UPGRADING HASIL BELAJAR SANTRI DI PESANTREN MAHASISWA THAYBAH SURABAYA - Muhammad Hambal Shafwan; Muhammad Sueb (Program Studi Pendidikan Agama Islam, 2023)
In the range of the academic year 2020/2021, the value of the Arabic language learning outcomes of the students of the Thaybah Islamic boarding school, Surabaya with the book of DL 1 did not show the expected level because it had not reached the standard value set by Thaybah's internal parties, 80.50. Then the researcher offered to collaborate with Thaybah to use a patterned Arabic learning module, the Deep Q & A written by the researcher as a supporting book in order to upgrade the value of student learning outcomes.This study has the following problem formulation: (1) How is the result of learningArabic from the Book of DL 1 of Pesma Thaybah students in the academic year 2020/2021?, (2) How is the implementation of the book of DL 1 learning method using patterned learning module, the Deep Q & A written by the researcher?, and (3) How to upgrade the results of learning Arabic from the Book of DL 1 for Pesma Thaybah students in the academic year 2021/2022? This thesis used descriptive qualitative research because it is in accordance with the themes and cases raised in this study. The results showed that the implementation of the Arabic book of DL 1 learning method using pattern learning module, the Deep Q & A written by the researcher succeeded in upgrading the average index of student learning outcomes in the range of academic year 2020/2021; it's just that it still hasn't been able to reach the standard level of value set by the internal Pesma Thaybah. This is possible because of the other factors affecting student learning outcomes that have not been identified in this study.